(untitled) (REVISTA NERA, 2015)
This research aimed to evaluate the agrifood system remaining marroom community Mandira, located in Cananéia/Sao Paulo/Brazil and relate it to the productive activities of families. The survey was conducted between the years 2011 and 2013, using quali-quantitative techniques with semi-structured interviews, informal conversations, participant observation and 24 hour recall. Families who have the economic base in agriculture have increased food diversity, control of production of food consumed. In contrast, families who have the economic base for the management of marine resources are more market-dependent, with higher consumption of processed items and less diversity of items consumed. Most families presents a process feed transition, leading to more westernized diet.